Influence of role models on the entrepreneurial skills of science and technology undergraduates - Kittichai Rajchamaha (2022)
Purpose: This study examines the perspectives of undergraduate science and technology students in Thailand regarding the influence of various role models on their entrepreneurial skills. Design/methodology/approach: This study employed the single case study research method. Purposive sampling was used to select the participants. The sample consisted of 142 key informants, whose responses were analysed using a direct content analysis method. Findings: From the students' perspectives, entrepreneurial role models indirectly influenced their entrepreneurial skills. Practical implications: The findings have clear implications for educators and policymakers. Educational institutions should design and implement educational strategies that help connect informal learning gained from the family with formal training at higher education institutions. On-the-job or apprenticeship training should also be included as a component of course content. Originality/value: Our findings regarding the influence of role models differ from those of previous studies in relation to two of the four role models considered here. First, according to the students, their family environment has no direct impact on their entrepreneurial skills. In addition, science- and technology-based educational environments should adopt an entrepreneurial orientation to help students understand various market and business pressures, which will enable them to make a positive contribution to the workplace.